O Léxico regional/popular de Graciliano Ramos em Caetés, são Bernardo e vidas secas: uma análise léxico-semântica - Marinho, Clécia Maria Nóbrega (2018)
The present work represents a linguistic study that describes the lexicon-semantic aspects in Caetés (1933), São Bernardo (1936) and Vidas Secas (1938), by Graciliano Ramos. Herein it is provided a glossary with the regional/popular léxicon of the writer which consists in a survey of regional/popular words and expressions from these works, supported by theoretical and methodological assumptions of Lexicology, Lexicography, including dialectical Lexicography, or regional, Semantics, as well as Dialectology, Sociolinguistics and Ethnolinguistics. Considering that its limits are defined by the regional/popular speech records contextualized in the literature studied and with the aim of proceeding to a lexiconsemantic description and analysis, and in the geo-socio-ethnolinguistic perspective, reaffirming the language-society-culture interface, the content of literary aspects and the processes inherent to it are not objects of study, they only support the analyses.